Cardiotoxicity screening of long‐term, breast cancer survivors—The CAROLE (Cardiac‐Related Oncologic Late Effects) Study. (10th July 2021) - Puckett, Lindsay L.; Saba, Shahryar G.; Henry, Sonia; Rosen, Stacey; Rooney, Elise; Filosa, Samaria L.; Gilbo, Philip; Pappas, Karalyn; Laxer, Alison; Eacobacci, Katherine; Kapyur, Amitha N.; Robeny, Justin; et al.
Abstract: Background: Long‐term breast cancer survivors are at risk for cardiotoxicity after treatment, but there is insufficient evidence to provide long‐term (~10 years) cardiovascular disease (CVD) screening recommendations. We sought to evaluate a tri‐modality CVD screening approach. Methods: This single‐arm, feasibility study enrolled 201 breast cancer patients treated ≥6 years prior without CVD at diagnosis. Patients were sub‐grouped: cardiotoxic (left‐sided) radiation (RT), cardiotoxic (anthracycline‐based) chemotherapy, both cardiotoxic chemotherapy and RT, and neither cardiotoxic treatment. Patients underwent electrocardiogram (EKG), transthoracic echocardiogram with strain (TTE with GLS), and coronary artery calcium computed tomography (CAC CT). The primary endpoint was preclinical or clinical CVD. Results: Median age was 50 (29–65) at diagnosis and 63 (37–77) at imaging; median interval was 11.5 years (6.7–14.5). Among sub‐groups, 44% had no cardiotoxic treatment, 31.5% had cardiotoxic RT, 16% had cardiotoxic chemotherapy, and 8.5% had both. Overall, 77.6% showed preclinical and/or clinical CVD and 51.5% showed clinical CVD. Per modality, rates of any CVD and clinical CVD were, respectively: 27.1%/10.0% on EKG, 50.0%/25.3% on TTE with GLS, and 50.8%/45.8% on CAC CT. No statistical difference was seen among the treatment subgroups (NS, χ 2 test, p  = 0.58/ p  = 0.15). Conclusion: This study identified a high incidence of CVD in heterogenous long‐term breast cancer survivors, most >10 years post‐treatment. Over half had clinical CVD findings warranting follow‐up and/or intervention. Each imaging test independently contributed to the detection rate. This provides early evidence that long‐term cardiac screening may be of value to a wider group of breast cancer survivors than previously recognized. Abstract : This study identified a high incidence of cardiovascular disease in a heterogenous group of long‐term (~10 years) breast cancer survivors; over half had clinical findings warranting follow‐up and/or intervention. This provides early evidence that cardiac screening may be of value to a wider group of long‐term breast cancer survivors than previously recognized.